2019
DOI: 10.3390/app9040672
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Path Planning for Multiple Mobile Robots via HAFSA and an Expansion Logic Strategy

Abstract: The cooperative path planning problem of multiple mobile robots in an unknown indoor environment is considered in this article. We presented a novel obstacle avoidance and real-time navigation algorithm. The proposed approach consisted of global path planning and local path planning via HAFSA (hybrid artificial fish swarm algorithm) and an expansion logic strategy. Meanwhile, a kind of scoring function was developed, which shortened the time of local path planning and improved the decision-making ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In previous research work, different methods were used to solve the multi-robot multi-goal path planning problem, that is, the authors in Huang et al (2019) considered the cooperative path planning problem of multiple mobile robots in an unknown indoor environment. They proposed a novel obstacle avoidance and real-time navigation algorithm.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research work, different methods were used to solve the multi-robot multi-goal path planning problem, that is, the authors in Huang et al (2019) considered the cooperative path planning problem of multiple mobile robots in an unknown indoor environment. They proposed a novel obstacle avoidance and real-time navigation algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, using multiple mobile robots rather than a single mobile robot has attracted many researchers' attention (Huang et al, 2019), and it has been widely used in industrial plants and warehouses (Liu et al, 2010). Optimizing the paths of the mobile robots that move simultaneously is a challenging problem (Nazarahari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[1] showed that the task can be transformed to an optimal assignment problem with mathematical modeling and suboptimal relaxations are available for the solution. Multiple mobile robots often experience path planning problems and a real-time navigation algorithm with obstacle avoidance has been suggested by Huang et al [2] based on a fish swarm algorithm to guide two phases of global and local path planning. In some environments, multiple mobile robots together manipulate an object in a cooperative way.…”
Section: Advanced Mobile Roboticsmentioning
confidence: 99%
“…As a typical representative of agents, multiple autonomous robots, including unmanned aerial vehicles (UAVs), automatic ground vehicles (AGVs), and unmanned underwater vehicles (UUVs), play an important role in military and civil fields [5][6][7][8][9][10][11][12][13]. To ensure robots carry out related work in our life efficiently and safely, path planning, which means finding a feasible path without collisions from the starting state to the target state, has been a hot research point in the field of mobile robot applications [14][15][16][17][18]. At present, path planning algorithms can be divided into global path planning algorithms and local path planning algorithms, which mainly include geometric algorithms, artificial potential field algorithms, grid-based search algorithms, and samplingbased algorithms.…”
Section: Introductionmentioning
confidence: 99%